Културолошките аспекти во теоретското творештво на архитект Живко Поповски : Мислевме дека можеме да живееме заборавајќи - Мери Батакоја (My University, 2017)
As an announcement of the book To Skopje With Love - Architectural Thought of Živko Popovski, this paper represents the most specific aspects of his theoretical work, recognizing them as extremely important to the cultural context of Macedonian architecture. His theoretical oeuvre, in official terms, is consisted of nearly seventy articles about architecture that are presently unavailable for the public due to their dispersion through national, regional and international architectural journals, literature and cultural journals, daily newspapers, faculty collections, private archives, etc. Because of that, our culture is deprived from these rare and direct testimonies of the development of the Macedonian architecture throughout nearly five decades, as well as from his own highly sensitized statements. The material aspects of one architectural opus are inseparable from the intangibility of architectural thought, so this book to come, has the goal to sensitize the Macedonian cultural world to consider architectural thought as cultural heritage, by which we remember, we graft and we communicate cultural values and upgrade one culture in continuity. In the context of his theoretical work, we must underline that Živko Popovski is also a pioneering editor of the first Macedonian architectural journal for culture of space “A:” which mobilized the Macedonian progressive architectural discourse. He is also one of the founders of the subject Architectural Theory and Research in the Faculty of Architecture in Skopje, which defines the architecture as an intellectual discipline that deeply reflects the cultural processes of the Macedonian society.
Cultural Aspects in the Theoretical Work of Architect Živko Popovski : The Impossibility of Future without Remembrance
Keywords: architectural theory, architectural thought, intangible cultural heritage, architecture and culture, Živko Popovski, Skopje